2018
DOI: 10.1534/genetics.118.301470
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Signaling Regulates Anthocyanin Biosynthesis Through a MAPK Cascade in Arabidopsis thaliana

Abstract: Anthocyanin accumulation specifically depends on sucrose (Suc) signaling. However, the molecular basis of this process remains unknown. In this study, in vitro pull-down assays identified ETHYLENE-INSENSITIVE3 (EIN3), a component of both sugar signaling or/and metabolism. This protein interacted with YDA, and the physiological relevance of this interaction was confirmed by in planta co-immunoprecipitation, yeast two-hybrid (Y2H) assay, and bimolecular fluorescence complementation. Ethylene insen-sitive3-like 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…All the primers used in the qRT-PCR analysis were designed using Vector NTI ( Table S6 ) without any interference of the conserved region, with an amplified product length of 150–300 bp. The cDNA concentration was adjusted based on the strawberry housekeeping gene FvRib413 ( Meng et al, 2018 ; Su, Wu & Cui, 2016 ). For qRT-PCR, each 20 µl reaction contained 10 µl of 2 × LightCycler 480 SYBR Green I Master mix (Cat# 4887352001, Roche), 2 µl of 50 × diluted cDNA, 0.4 µl of each primer, and 7.2 µl of ddH 2 O, and the data were processed with LightCycler ® 480 software (Roche, China).…”
Section: Methodsmentioning
confidence: 99%
“…All the primers used in the qRT-PCR analysis were designed using Vector NTI ( Table S6 ) without any interference of the conserved region, with an amplified product length of 150–300 bp. The cDNA concentration was adjusted based on the strawberry housekeeping gene FvRib413 ( Meng et al, 2018 ; Su, Wu & Cui, 2016 ). For qRT-PCR, each 20 µl reaction contained 10 µl of 2 × LightCycler 480 SYBR Green I Master mix (Cat# 4887352001, Roche), 2 µl of 50 × diluted cDNA, 0.4 µl of each primer, and 7.2 µl of ddH 2 O, and the data were processed with LightCycler ® 480 software (Roche, China).…”
Section: Methodsmentioning
confidence: 99%
“…It has been proved that glucose can be converted into sucrose within a few hours and further induced anthocyanin accumulation in Arabidopsis (Solfanelli et al 2006). The increased sucrose was found to stimulate anthocyanin biosynthesis in Arabidopsis loss-of-function mutants YDA and in the hypocotyls of radish sprouts (Su et al 2016, Meng et al 2018. Therefore, the positive correlation between sucrose content and anthocyanin accumulation is conserved in Brassicaceae family.…”
Section: Discussionmentioning
confidence: 98%
“…In several plant species, it has been demonstrated that sugars regulate the accumulation of flavonoids. Anthocyanins are a widespread class of plant flavonoids and their accumulation is modulated by sucrose, a well-characterized endogenous developmental signal (Solfanelli et al, 2006; Meng et al, 2018). Whole-genome transcript profiling reveals that sucrose treatment up-regulated the flavonoid and anthocyanin biosynthetic pathway and affects both flavonoid and anthocyanin contents (Solfanelli et al, 2006).…”
Section: Discussionmentioning
confidence: 99%